KEPERCAYAAN EKSISTENSIAL REMAJA JAWA (Suatu Studi Asuhan dalam Keluarga di Desa Tlogorejo, Purwodadi, Purworejo,Jawa Tengah) - Muhammad Idrus (Jurnal Kependidikan, 2005)
Abstract The purpose of this research is to find out the influence  of parenting style and peers interaction on identify status, existential belief (faith) and the Javanese’s adolescent culture value orientation. Structural equation model (SEM) is designed for more comprehensive analyzing the hypothesis ed model, which involves 318 respondents adolescence of Tegalrejo’s village. The data are collected using questionnaire and scale. SEM is used to Lisrel 8.30 program. The result of the analysis yields several conclusions: (1) the constructed model fit with the empirical data (2) existential belief is not growing with chronological age(3) parenting style does not have a direct effect on identity status. The indirect effects parenting style on identity status through cultural value orientation. There were direct effect and indirect effect parenting styles on adolescent’s existential belief (4) peer interaction has either direct or indirect effect on identity status, adolescents’ existential belief and cultural value orientation. Furthermore it is also known, that there is indirect effect peer interaction  on adolescent’s existential belief through identity status and cultural value orientation. (5) cultural value orientation has significant  positive effect on identity status. Beside that cultural value orientation has positive effect either direct or indirect effect on existential belief. Indirect effect cultural value orientation on existential belief through identity status. (6) this research showed triadic interaction between peer interaction, cultural value orientation and identity status. Other triadic interaction emerges in the interaction between cultural value orientation, identity status and existential belief. Keywords: existential belief, parenting style, peer interaction, cultural value orientation, identity status.